Synthesis of Fe3O4 Nanoparticles from Ironstone Prepared by Polyethylene Glycol 4000 - Astuti, Astuti; Claudia, Geby; Noraida, Noraida; Ramadhani, Melvira (Makara Journal of Science, 2013)
This study reports the modification of the preparation method of Fe3O4 nanoparticles, which consists of two stages, beginning with the destruction and separation of iron ore from ironstone. Then, the Fe3O4 nanoparticles are synthesized using the coprecipitation method with magnetite (Fe3O4). Polyethylene glycol (PEG) 4000, a readily available chemical, was introduced in varying amounts into the reactions. The ratio of Fe3O4 powder and PEG 4000 is 1:3, 1:4, and 1:5, respectively, and the effects of the PEG 4000 on the morphology, crystalline size, and magnetic properties of the products were studied. It was shown that the particle and crystalline sizes decreased when the concentration of PEG 4000 increased. Additionally, the smallest Fe3O4 nanoparticles were around 50-60 nm, and semispherical nanoparticles were formed. The reduction of the crystalline size with the increase in PEG 4000 was shown by using XRD patterns, with the crystalline size being about 30 nm at a ratio of 1:5 Fe3O4 and PEG 4000, respectively. The hysteresis loop showed low coercivity, indicating that all products were soft magnetic.